Reassessing the most popularly suggested measurement models and measurement invariance of the Maslach Burnout Inventory - human service survey among Vietnamese healthcare professionals - Bui, Thi Hong Thai; Tran, Thi Minh Duc; Nguyen, Thi Nhu Trang; Vu, Thy Cam; Ngo, Xuan Diep; Nguyen, Thi Hang Phuong; Do, Thi Le Hang (Health psychology & behavioral medicine, 2022)
Despite its popularity, Maslach Burnout Inventory-Human Service Survey (MBI-HSS)'s factorial structure has been subject to considerable debate, and its measurement invariance (MI) is seldomly examined. This cross-sectional study aims at reassessing the most popularly suggested structures of this instrument, namely the 20- and 22-item three-factor model on Vietnamese healthcare professionals. It also examines the MI of MBI-HSS across genders, occupations, and mental health conditions. Self-administered questionnaires were sent out to 1500 doctors and nurses working at 15 hospitals in big cities in Vietnam in September and October 2020, and 1162 valid questionnaires were collected. The questionnaire consists of three sets of questions covering (1) demographic information of participants; (2) MBI-HSS questionnaire; and (3) The 21-item version of the Depression-Anxiety-Stress Scale. MBI-HSS scale was validated on Vietnamese sample for the first time; therefore, we used the repeated forward-backward procedure to translate this scale into Vietnamese. To examine which model best fits the data, a series of Confirmatory Factor Analysis (CFA) was used to test the model fit of correlated three-factor model, second-order hierarchical model, and bi-factor model. The reliability of the MBI-HSS was assessed using Cronbach's α coefficients. Then, multiple-group CFA (MGCFA) was applied to determine whether the MBI-HSS has a similar structure between groups different in gender, occupation, and mental health condition. Our findings confirmed that the 22-item MBI-HSS best fit the data, and this scale measures three distinct but related aspects of burnout, including Emotional Exhaustion, Depersonalization, and Personal Accomplishment. The MI of MBI-HSS across genders and occupations was also confirmed. However, data did not fit well with group at risk for common mental health disorders. It can be concluded that the Vietnamese version of MBI-HSS is a valid measure to assess burnout level of healthcare professionals in Vietnam who are not at risk for mental health disorders.